Share Price Trigger in Manufacturing Companies on The Indonesia Stock Exchange - Nuryani, Ni Nyoman Juli; Gorda, A. A.N. Oka Suryadinatha; Sulistyorini, Ery (University of Merdeka Malang, 2023)
This study aims to examine the effect of Earning Per Share (EPS), Net Profit Margin (NPM), Gross Profit Margin (GPM), and Total Asset Turnover (TATO) on stock prices in manufacturing companies in the food and beverages sector listed on the Indonesia Stock Exchange (IDX) with an observation period of 2018-2022. The population and sample in this study are the quarterly financial statements of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange. The sampling method used is purposive sampling, with a total sample of 252 quarterly financial statements from 12 companies. The data used in this research is secondary data. Then, the data collected was tested by multiple linear regression analysis, which was processed using the SPSS version 18 application. The results showed that EPS and NPM have a positive and significant effect on stock prices, while GPM has no significant effect on stock prices, and TATO has a negative and significant impact on stock prices. Simultaneously, EPS, NPM, GPM, and TATO positively and significantly affect stock prices with a coefficient of determination of 67.4%.DOI: 10.26905/jkdp.v27i3.11747